Pregnant women voice their concerns and birth expectations during the COVID-19 pandemic in Italy (2020)
Background: In March 2020, COVID-19 was declared to be a pandemic. While data suggests that COVID-19 is not associated with significant adverse health outcomes for pregnant women and newborns, the psychological impact on pregnant women is likely to be high. Aim: The aim was to explore the psychological impact of the COVID-19 pandemic on Italian pregnant women, especially regarding concerns and birth expectations. Methods: A cross-sectional online survey of pregnant women in Italy was conducted. Responses were analysed for all women and segregated into two groups depending on previous experience of pregnancy loss. Analysis of open text responses examined expectations and concerns before and after the onset of the pandemic. Findings: Two hundred pregnant women responded to the first wave of the survey. Most (n = 157, 78.5%) had other children and 100 (50.0%) had a previous history of perinatal loss. ‘Joy’ was the most prevalent emotion expressed before COVID-19 (126, 63.0% before vs 34, 17.0% after; p<0.05); fear was the most prevalent after (15, 7.5% before vs 98, 49.0% after; p<0.05). Positive constructs were prevalent before COVID-19, while negative ones were dominant after (p<0.05). Across the country, women were concerned about COVID-19 and a history of psychological disorders was significantly associated with higher concerns (p<0.05). A previous pregnancy loss did not influence women’s concerns. Conclusions: Women’s expectations and concerns regarding childbirth changed significantly as a result of the COVID-19 pandemic in Italy. Women with a history of psychological disorders need particular attention as they seem to experience higher levels of concern.